Silicon-carbon negative electrode material with carbon tube structure and preparation method of silicon-carbon negative electrode material

By introducing carbon tube structure into silicon carbon negative electrode material, the cycle stability and volume expansion problems of silicon-based negative electrode material in lithium-ion batteries are solved, and higher specific capacity and cycling performance are achieved, improving the battery's fast charging capability .

CN119480970APending Publication Date: 2025-02-18EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411590692.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

Smart Images

  • Figure CN119480970A_ABST
    Figure CN119480970A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion batteries, and provides a silicon-carbon negative electrode material with a carbon tube structure and a preparation method thereof, the negative electrode material comprises the following raw materials by weight: 45-60 parts of a reducing agent, 5-15 parts of a catalyst and 35-45 parts of a silicon-based intermetallic compound; according to the preparation method provided by the invention, due to the addition of the catalyst, the externally coated carbon layer contains a certain amount of multi-walled carbon nanotubes, the conductivity and mechanical strength of the carbon tubes are higher than those of a common carbon layer, and the carbon tubes also have excellent structural flexibility and tortuosity, so that the overall volume expansion can be effectively relieved, and the interface stability can be kept; the transfer of electrons and ions is enhanced, and the cycling stability of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries, and specifically relates to a silicon-carbon negative electrode material with a carbon tube structure and a preparation method thereof. Background Art

[0002] As the current mainstream energy storage system, lithium-ion batteries have great advantages in voltage, life, self-discharge and energy density, so they are widely used in electric vehicles and advanced portable electronic devices. Faced with strong market driving force and policy support, improving energy density and fast charging performance is an inevitable trend in the development of lithium-ion batteries to meet the endurance requirements of lithium-ion batteries in different scenarios. At present, the positive electrode material has reached its capacity limit in process use (lithium iron phosphate 175mAh / g, nickel-cobalt-manganese ternary positive electrode 205mAh / g, lithium manganese oxide 148mAh / g), and further research on positive electrode materials is of little significance; graphite is the most commonly used commercial negative electrode material, but its capacity is only 372mAh / g, which is difficult to meet the rapidly growing demand for capacity density of energy storage devices. Silicon is the material with the highest specific capacity among the currently known negative electrode materials, and it is abundant in the earth's crust and is an ideal negative electrode material for lithium-ion batteries. However, the silicon negative electrode has problems of poor conductivity and volume expansion during the charging and discharging process, making it difficult to achieve large-scale application;

[0003] In order to better utilize the advantages of high specific capacity of silicon-based negative electrodes, many researchers are committed to improving the cycle stability of silicon-based negative electrodes. The routes of silicon-based negative electrodes mainly include silicon-oxygen routes, pre-lithiation silicon-oxygen materials and silicon-carbon materials. Among them, some progress has been made by optimizing the structure of silicon-carbon materials to alleviate the volume expansion effect, such as multiple coatings and pomegranate structure design. But overall, these modification methods have failed to achieve the expected performance, especially the cycle performance needs to be further improved.

[0004] To this end, those skilled in the art have proposed a silicon-carbon negative electrode material with a carbon tube structure and a preparation method thereof to solve the problems raised by the background technology. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a silicon-carbon negative electrode material with a carbon tube structure and a preparation method thereof to solve the problems in the prior art.

[0006] A silicon-carbon negative electrode material with a carbon tube structure comprises the following raw materials in parts by weight: 45-60 parts of a reducing agent, 5-15 parts of a catalyst and 35-45 parts of a silicon-based intermetallic compound.

[0007] Preferably, the reducing agent is one of sodium borohydride, potassium borohydride, lithium borohydride, sodium thioborohydride and lithium tri-sec-butylborohydride, the catalyst is one of nickel ferrite, ferrocene, cobalt nitride nanoparticles and nickel chloride, and the silicon-based intermetallic compound is one of Mg2Si, CaS i2, NiSi and FeSi.

[0008] A method for preparing a silicon-carbon negative electrode material having a carbon tube structure comprises the following steps:

[0009] S1. Dispersing the reducing agent alone in an isopropanol solution, and dispersing the catalyst and the silicon-based metal compound together in the isopropanol solution, mixing all the solutions evenly after ultrasonic dispersion treatment, and then transferring them to a crucible for vacuum drying to obtain a solid mixture of the reducing agent, the catalyst and the silicon-based metal oxide;

[0010] S2. The solid mixture is moved to a tube furnace, first purged with argon for 0.5-1h, then the temperature is increased, and carbon dioxide is introduced continuously for a long time to react. After cooling, the mixture is taken out, acid-washed, filtered and dried to finally obtain a silicon-carbon negative electrode material with a carbon tube structure.

[0011] Preferably, in step S1, the content of the isopropanol solution is 10-30 mL, the ultrasonic dispersion time is 0.5-3 h, the vacuum drying temperature is 80-120° C., and the time is controlled to be 0.5-3 h.

[0012] Preferably, in step S2, the tube furnace needs to ensure airtightness, and the solid mixture needs to be placed in an argon atmosphere.

[0013] Preferably, in step S2, the temperature is increased at a rate of 1-10°C / min. -1 The reaction temperature is 600-800℃, the reaction time is controlled at 2-8h, and the flow rate of carbon dioxide is 20-80mL / min -1 .

[0014] Preferably, in step S2, the pickling and filtration need to pass through three solutions of hydrochloric acid, anhydrous ethanol and deionized water, and the concentration of hydrochloric acid is 0.5-1 mol / L. -1 .

[0015] Preferably, in step S2, the drying can be performed by heating and drying in a vacuum drying oven or by air drying.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. In the preparation method provided by the present invention, due to the addition of the catalyst, the externally coated carbon layer has a certain content of multi-walled carbon nanotubes, and the conductivity and mechanical strength of the carbon tubes are stronger than those of ordinary carbon layers. It also has excellent structural flexibility and tortuosity, can effectively alleviate the overall volume expansion, maintain interface stability, enhance the transfer of electrons and ions, and improve the cycle stability of lithium-ion batteries.

[0018] 2. The preparation method provided by the present invention increases the internal transmission channels of electrons and ions, thereby improving the specific capacity and cycle performance, and the externally coated carbon layer is uniform and dense, thereby optimizing the surface coating structure, which can significantly improve the fast charging capability of the battery prepared therefrom. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the XRD pattern of the silicon-carbon material with carbon tube structure prepared in Example 3 of the present invention;

[0020] Figure 2 This is a Raman spectrum of the silicon-carbon material with a carbon tube structure prepared in Example 3 of the present invention;

[0021] Figure 3 This is a SEM image of the silicon-carbon material with a carbon tube structure prepared in Example 3 of the present invention;

[0022] Figure 4 TEM image of the silicon-carbon material with carbon tube structure prepared in Example 3 of the present invention;

[0023] Figure 5 This is a first charge and discharge curve diagram of the silicon-carbon material with a carbon tube structure prepared in Example 3 of the present invention;

[0024] Figure 6 A comparison diagram of the ratio of the silicon-carbon anode with a carbon tube structure of the present invention and the traditional commercial pure silicon anode material;

[0025] Figure 7 This is a cycle comparison diagram of the silicon-carbon negative electrode with a carbon tube structure of the present invention and a traditional commercial pure silicon negative electrode material. DETAILED DESCRIPTION

[0026] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0027] Embodiment 1: The present invention provides a silicon-carbon negative electrode material with a carbon tube structure, comprising the following raw materials in parts by weight: 45-60 parts of a reducing agent, 5-15 parts of a catalyst and 35-45 parts of a silicon-based metal compound.

[0028] Furthermore, the reducing agent is one of sodium borohydride, potassium borohydride, lithium borohydride, sodium thioborohydride and lithium tri-sec-butylborohydride, the catalyst is one of nickel ferrite, ferrocene, cobalt nitride nanoparticles and nickel chloride, and the silicon-based intermetallic compound is one of Mg2Si, CaSi2, NiS i and FeSi.

[0029] As can be seen from the above, the reducing agent is selected from one of sodium borohydride, potassium borohydride, lithium borohydride, sodium thioborohydride and lithium tri-sec-butylborohydride. These raw materials have strong reducing properties and can effectively reduce silicon-based metal compounds during the preparation process. The catalyst is selected from one of nickel ferrite, ferrocene, cobalt nitride nanoparticles and nickel chloride, which can accelerate the reaction rate and improve the reaction efficiency during the preparation process, thereby helping to form a carbon tube structure silicon-carbon negative electrode material with excellent performance. The silicon-based metal compound is selected from one of Mg2Si, CaS i2, NiSi and FeS i. These silicon-based metal compounds have excellent electrical and mechanical properties and are important raw materials for preparing high-performance silicon-carbon negative electrode materials. They can be effectively combined with the reducing agent and the catalyst to form a negative electrode material with excellent conductivity and high energy density, thereby improving the performance of lithium-ion batteries.

[0030] Embodiment 2: This embodiment is basically the same as the previous embodiment, except that a method for preparing a silicon-carbon negative electrode material having a carbon tube structure comprises the following steps:

[0031] S1. Dispersing the reducing agent alone in an isopropanol solution, and dispersing the catalyst and the silicon-based metal compound together in the isopropanol solution, mixing all the solutions evenly after ultrasonic dispersion treatment, and then transferring them to a crucible for vacuum drying to obtain a solid mixture of the reducing agent, the catalyst and the silicon-based metal oxide;

[0032] S2. The solid mixture is moved to a tube furnace, first purged with argon for 0.5-1h, then the temperature is increased, and carbon dioxide is introduced continuously for a long time to react. After cooling, the mixture is taken out, acid-washed, filtered and dried to finally obtain a silicon-carbon negative electrode material with a carbon tube structure.

[0033] Among them, dispersing the reducing agent alone in the isopropanol solution, and dispersing the catalyst and the silicon-based metal compound together in the isopropanol solution, helps to achieve uniform mixing of these components. This uniform mixing can ensure the uniformity and consistency of the reaction. Vacuum drying can remove the isopropanol in the mixture to prevent adverse reactions or safety hazards caused by the presence of isopropanol in subsequent high-temperature reactions.

[0034] Before carrying out the reaction in the tubular furnace, argon purging is performed for 0.5-1h. Argon, as an inert gas, can remove the air in the tubular furnace to prevent the oxygen in the air from interfering with the reaction or causing oxidation reaction. This step can protect the material from air oxidation and ensure the smooth reaction.

[0035] Further, in step S1, the content of the isopropanol solution is 10-30 mL, the ultrasonic dispersion time is 0.5-3 h, the vacuum drying temperature is 80-120° C., and the time is controlled to be 0.5-3 h.

[0036] Furthermore, in step S2, the tube furnace needs to ensure airtightness, and the solid mixture needs to be placed in an argon atmosphere.

[0037] Furthermore, in step S2, the temperature is increased at a rate of 1-10°C / min. -1 The reaction temperature is 600-800℃, the reaction time is controlled at 2-8h, and the flow rate of carbon dioxide is 20-80mL / min -1 .

[0038] The temperature increase rate is 1-10℃ / min -1 Controlling the reaction temperature to 600-800°C can increase the reaction rate and the purity of the product while avoiding the occurrence of side reactions. Controlling the time to 2-8h also helps to ensure the full progress of the reaction and the stable generation of the product. By introducing carbon dioxide for a long time for the reaction, carbon dioxide as a reactant helps to form a silicon-carbon negative electrode material with a carbon tube structure.

[0039] Furthermore, in step S2, pickling and filtration need to pass through three solutions of hydrochloric acid, anhydrous ethanol and deionized water, and the concentration of hydrochloric acid is 0.5-1mol / L. -1 .

[0040] Among them, pickling can remove impurities and unreacted substances in the reaction products, improve the purity of the products, and generate silicon nanoparticles with a porous structure. This porous structure can alleviate the volume expansion of silicon during the charging and discharging process. Filtration can further separate and purify the products and remove residual liquid and impurities.

[0041] Furthermore, in step S2, the drying may be performed by heating and drying in a vacuum drying oven or by air drying.

[0042] Among them, drying can remove moisture and other volatile substances in the product to ensure the stability and consistency of the product.

[0043] It can be seen from this that the preparation method provided by the present invention uses the generated metal oxide as a sacrificial template, and generates silicon nanoparticles with a porous structure after acid washing. This silicon negative electrode not only has a small particle size, but also its volume expansion during charging and discharging will be limited within these pore structures.

[0044] Embodiment 3: This embodiment is basically the same as the previous embodiment, except that a method for preparing a silicon-carbon negative electrode material having a carbon tube structure is provided:

[0045] First, 1 g of sodium borohydride, 0.05 g of nickel chloride and 0.2 g of magnesium silicide were each dispersed in a certain amount of isopropanol solution. After ultrasonic dispersion treatment for 30 minutes, all the solutions were mixed evenly and then transferred to a crucible for vacuum drying for 2 hours at 90°C to obtain a solid mixture of sodium borohydride, nickel metal particles and magnesium silicide.

[0046] The solid mixture was transferred to a tube furnace, purged with argon for 1 hour, and then heated to 700°C, and carbon dioxide was continuously introduced for 6 hours for reaction. After cooling, the mixture was taken out, acid-washed, filtered and dried to finally obtain a silicon-carbon negative electrode material with a carbon tube structure. The silicon-carbon negative electrode material with a carbon tube structure was scanned by an X-ray diffractometer, a Raman spectrometer, a scanning electron microscope and a transmission electron microscope to generate XRD patterns, Raman spectra, SEM patterns and TEM patterns, as shown in FIG. Figure 1-Figure 4 shown.

[0047] Embodiment 4: This embodiment is basically the same as the previous embodiment, except that: Application of a silicon-carbon negative electrode material having a carbon tube structure:

[0048] The silicon-carbon negative electrode material prepared in the above embodiment was fully stirred and mixed with a conductive agent and a binder in a ratio of 6:2:2, and the obtained slurry was evenly coated on a copper foil with a coating thickness of 30 um. After vacuum drying at 100°C for 12 hours, the negative electrode material was obtained. The negative electrode sheet was cut into 12 mm discs, a lithium sheet was used as a counter electrode, and cegard2500 was used as a diaphragm. Lithium hexafluorophosphate was dissolved in an organic solvent with a volume ratio of EC:DMC:EMC=1:1:1 to obtain an electrolyte of lithium hexafluorophosphate with a concentration of 1 M. A CR2032 battery shell was used as a battery shell, and the battery was assembled in the order of negative electrode-electrolyte-diaphragm-electrolyte-lithium sheet-gasket-spring sheet. After being taken out, it was compacted and a constant current charge and discharge test was performed. The test results are as follows: Figure 5 shown.

[0049] The rate performance of the conventional commercial pure silicon negative electrode material and the silicon-carbon negative electrode material with carbon tube structure prepared by the present invention at different current densities was tested, and the results are as follows: Figure 6As shown in Figure 2, the specific capacity of the traditional commercial pure silicon negative electrode material rapidly decays to 21.9% of the original capacity after the first 10 cycles. As the current density increases further, it causes irreversible capacity loss to the electrode. However, the silicon-carbon negative electrode material has a high specific capacity of 21.9% at 100 mA g -1 When cycled at a current of -1 , at 2A g -1 When cycling at a current of , the capacity can also be maintained at 763mAh g -1 ; When the current density returns to 100 mA g -1 Afterwards, the capacity retention rate is as high as 86.8%, indicating that the silicon-carbon negative electrode material has good rate performance. It can be seen that the preparation method provided by the present invention increases the internal electron and ion transmission channels, thereby improving the specific capacity and cycle performance, and the external coating carbon layer is uniform and dense, thereby optimizing the surface coating structure, which can significantly improve the fast charging capability of the battery prepared therefrom.

[0050] At the same time, the conventional commercial pure silicon negative electrode material and the silicon-carbon negative electrode material with carbon tube structure prepared by the present invention were compared at 500 mA g -1 The cycling performance was tested at a current density of Figure 7 As shown in the figure, it can be seen that the specific capacity of the traditional commercial pure silicon negative electrode material drops rapidly to 500 mAh g in the fourth cycle. -1 After 120 cycles, the specific capacity is only 56.8 mAh g -1 The silicon-carbon anode material showed good cycle stability in 120 cycles, and the specific capacity remained at 1000 mAh g after the test. -1 The Coulomb efficiency is about 99%, which shows that in the preparation method provided by the present invention, due to the addition of the catalyst, the externally coated carbon layer has a certain content of multi-walled carbon nanotubes, the conductivity and mechanical strength of the carbon tubes are stronger than those of ordinary carbon layers, and the carbon tubes also have excellent structural flexibility and tortuosity, which can effectively alleviate the overall volume expansion and maintain interface stability; enhance the transfer of electrons and ions, and improve the cycle stability of lithium-ion batteries.

[0051] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A silicon-carbon negative electrode material with a carbon tube structure, characterized in that: The invention comprises the following raw materials in parts by weight: 45-60 parts of a reducing agent, 5-15 parts of a catalyst and 35-45 parts of a silicon-based intermetallic compound.

2. A silicon-carbon negative electrode material with a carbon tube structure as claimed in claim 1, characterized in that: The reducing agent is one of sodium borohydride, potassium borohydride, lithium borohydride, sodium thioborohydride and lithium tri-sec-butylborohydride, the catalyst is one of nickel ferrite, ferrocene, cobalt nitride nanoparticles and nickel chloride, and the silicon-based intermetallic compound is one of Mg2Si, CaSi2, NiSi and FeSi.

3. A method for preparing a silicon-carbon negative electrode material with a carbon tube structure, the silicon-carbon negative electrode material with a carbon tube structure as claimed in any one of claims 1 to 2, characterized in that: The steps include: S1. Dispersing the reducing agent alone in an isopropanol solution, and dispersing the catalyst and the silicon-based metal compound together in the isopropanol solution, mixing all the solutions evenly after ultrasonic dispersion treatment, and then transferring them to a crucible for vacuum drying to obtain a solid mixture of the reducing agent, the catalyst and the silicon-based metal oxide; S2. The solid mixture is moved to a tube furnace, first purged with argon for 0.5-1h, then the temperature is increased, and carbon dioxide is introduced continuously for a long time to react. After cooling, the mixture is taken out, acid-washed, filtered and dried to finally obtain a silicon-carbon negative electrode material with a carbon tube structure.

4. A method for preparing a silicon-carbon negative electrode material having a carbon tube structure as claimed in claim 3, characterized in that: In step S1, the content of the isopropanol solution is 10-30 mL, the ultrasonic dispersion time is 0.5-3 h, the vacuum drying temperature is 80-120° C., and the time is controlled to be 0.5-3 h.

5. The method for preparing a silicon-carbon negative electrode material having a carbon tube structure as claimed in claim 3, characterized in that: In step S2, the tube furnace must ensure airtightness, and the solid mixture must be placed in an argon atmosphere.

6. A method for preparing a silicon-carbon negative electrode material having a carbon tube structure as claimed in claim 3, characterized in that: In step S2, the temperature is increased at a rate of 1-10°C / min. -1 The reaction temperature is 600-800°C, the reaction time is controlled at 2-8h, and the flow rate of the carbon dioxide is 20-80mL / min -1 .

7. A method for preparing a silicon-carbon negative electrode material having a carbon tube structure as claimed in claim 3, characterized in that: In step S2, the acid washing and filtration need to pass through three solutions of hydrochloric acid, anhydrous ethanol and deionized water, and the concentration of the hydrochloric acid is 0.5-1 mol / L -1 .

8. The method for preparing a silicon-carbon negative electrode material having a carbon tube structure as claimed in claim 3, characterized in that: In step S2, the drying may be performed by heating and drying in a vacuum drying oven or by air drying.